Acute Issues of Cognitive Modeling of Semi-Structured and Poorly Formalized Systems - A. A. Mikryukov; M. E. Mazurov; D. A. Suzdalsky; K. E. Chikunov (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
The article studies specific features of mathematic tools of cognitive modeling meant to resolve tasks of analyzing functioning and forecasting the development of semi-structured and poorly formalized systems. Semi-structured systems are complicated dynamic systems, where human factor plays an important role. These systems are characterized by uncertainty of data-in and data-out and they cannot be described by precise formal dependencies. Difficulty of studying poorly formalized systems is connected with the necessity to take into account various and often contradicting figures and criteria, which would not allow us to describe formally components of the system and its functions. To model system of this class mathematic tools of cognitive modeling can be used on the basis of cognitive maps. Cognitive map can provide an integral idea of semi-structured and poorly formalized system in the form of a graph, which can help conduct scenario modeling of the system, prepare recommendations for its stable functioning and resolve problems of forecasting its development. The authors investigate applied aspects and specific features of methods of cognitive modeling. Apart from that they provided description of mathematic tools and their possibilities and put forward mathematic approach to solving tasks of cognitive modeling and gave examples of its use.